Macronutrient supply, uptake and recycling in the coastal ocean of the west Antarctic Peninsula. (May 2017) - Henley, Sian F.; Tuerena, Robyn E.; Annett, Amber L.; Fallick, Anthony E.; Meredith, Michael P.; Venables, Hugh J.; Clarke, Andrew; Ganeshram, Raja S.
Abstract: Nutrient supply, uptake and cycling underpin high primary productivity over the continental shelf of the west Antarctic Peninsula (WAP). Here we use a suite of biogeochemical and isotopic data collected over five years in northern Marguerite Bay to examine these macronutrient dynamics and their controlling biological and physical processes in the WAP coastal ocean. We show pronounced nutrient drawdown over the summer months by primary production which drives a net seasonal nitrate uptake of 1.83 mol N m -2 yr -1, equivalent to net carbon uptake of 146 g C m -2 yr -1 . High primary production fuelled primarily by deep-sourced macronutrients is diatom-dominated, but non-siliceous phytoplankton also play a role. Strong nutrient drawdown in the uppermost surface ocean has the potential to cause transient nitrogen limitation before nutrient resupply and/or regeneration. Interannual variability in nutrient utilisation corresponds to winter sea ice duration and the degree of upper ocean mixing, implying susceptibility to physical climate change. The nitrogen isotope composition of nitrate (δ 15 NNO3 ) shows a utilisation signal during the growing seasons with a community-level net isotope effect of 4.19 ± 0.29‰. We also observe significant deviation of our data from modelled and observed utilisation trends, and argue that this is driven primarily by water column nitrification and meltwater dilution of surface nitrate. This study is important because it provides a detailed description of the nutrient biogeochemistry underlying high primary productivity at the WAP, and shows that surface ocean nutrient inventories in the Antarctic sea ice zone can be affected by intense recycling in the water column, meltwater dilution and sea ice processes, in addition to utilisation in the upper ocean.